Early stroke case-fatality rates in three hospital registries in the Northeast and Southeast of Brazil - Tiótrefis G. Fernandes; Alessandra C. Goulart; Tania F. Campos; Neide M. G. Lucena; Karen L. A. Freitas; Cláudia M. Trevisan; Isabela M. Benseñor; Paulo A. Lotufo (Arquivos de Neuro-Psiquiatria)
Few studies have addressed early cerebrovascular lethality in Brazil. OBJECTIVE: To evaluate 10 and 28-day stroke case-fatality rates in three hospitals in three Brazilian cities. METHODS: We described the stroke registries in São Paulo, João Pessoa, and Natal. RESULTS: Out of a total of 962 first-ever events (mean age, 68.1 years-old; 53% men), 83.6% (804 cases) were classified as ischemic and 16.4% (158) as hemorrhagic stroke. Overall, the case-fatality rates and 95% confidence intervals (95%CI) for hemorrhagic stroke events were higher than for ischemic events, both at 10 (12.3%; 95%CI 7.2-17.4 versus 7.0%; 95%CI 5.3-8.8) and at 28 days (19.8%; 95%CI 13.6-26.0 versus 11.1%; 95%CI 8.9-13.3). CONCLUSIONS: We did not find any substantial differences in early case-fatality rates according to stroke subtypes, when comparing the three centers.